Characterisation of Pulsed-Fibre-Laser-Perforated Polymeric Food Package Films. Issue 4 (May 2018) - Ovaska, Sami-Seppo; Leminen, Ville; Tanninen, Panu; Manninen, Matti; Mielonen, Katriina; Matthews, Sami; Lindell, Henry; Backfolk, Kaj
A packaging material requires a proper interaction with regard to water vapour transmission between the product and the outside environment. For many fresh food products such as bakery goods, fruits, and vegetables, microperforation is utilised to extend the shelf life of the foodstuff and to provide better food quality. The microperforation potential of five commercial polymeric films has been evaluated using a pulsed fibre laser technique, and significant differences were found between the films in the penetration of the laser beam and in the diameter of the perforation. Breathable polymeric packaging films were prepared with an average laser power of 20 W and a pulse duration of 200 ns. The numbers of holes (80 μm in diameter) in the films were approx. 2000 holes/m 2 and 4000 holes/m 2 . As expected, the number of perforations affected the water vapour transmission (WVT): the WVT was 11 g/m 2 /d for unperforated film, and 60 g/m 2 /d for the film with 4000 holes/m 2, indicating that the fibre laser can be used successfully for microperforating this type of polymeric films. However, microscopic and microtomographic analyses revealed major differences in hole formation behaviour and in the wall structures of the microperforations.